2013
DOI: 10.1146/annurev-soc-071312-145544
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Variation in Assortative Mating: Causes and Consequences

Abstract: Assortative mating fundamentally shapes the characteristics of families and the reproduction of populations. It organizes people into families and determines the characteristics of parents. In this article, I review the literature on the causes and consequences of trends and variation in assortative mating. Explanations for why assortative mating varies have been dominated by modernization theory, but perspectives emphasizing economic inequality and gender inequality have gained momentum in recent years. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
534
1
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(565 citation statements)
references
References 125 publications
9
534
1
21
Order By: Relevance
“…As observed by others, geographic, ethnic, and cultural determinants of spousal assortment declined over the course of the 20th century while assortment on individual attributes increased. In line with these observations, we hypothesized that genetic assortment on the social, mental, and physical characteristics we studied would have increased in tandem with the rising phenotypic assortative mating observed by others (33,34). We found that husbands and wives in the HRS were similar to each other, both phenotypically and genetically.…”
Section: Resultssupporting
confidence: 54%
“…As observed by others, geographic, ethnic, and cultural determinants of spousal assortment declined over the course of the 20th century while assortment on individual attributes increased. In line with these observations, we hypothesized that genetic assortment on the social, mental, and physical characteristics we studied would have increased in tandem with the rising phenotypic assortative mating observed by others (33,34). We found that husbands and wives in the HRS were similar to each other, both phenotypically and genetically.…”
Section: Resultssupporting
confidence: 54%
“…assortative mating | genomic ancestry | homogamy M ate selection in human populations is a topic of broad general and academic interest, with important implications for economics (1), sociology (2), psychology (3), and genetics (4,5). Studies from all of these fields have uncovered myriad genetic and socioeconomic factors that are correlated between partners.…”
mentioning
confidence: 99%
“…Some commentators have concluded that these economic processes have deepened the earning differences between low and high-educated individuals (Förster 2000). Similarly, the status attainment hypothesis used in sociology postulates that modernisation gives more importance to achieved characteristics such as education than to ascribed characteristics such as ethnicity or social origin (Schwartz 2013;Goode 1963).…”
Section: Assortative Mating and Educationmentioning
confidence: 99%
“…Assortative mating can contribute to the transmission of economic status (Kremer 1997;Chadwick and Solon 2002;Black and Devereux 2011) and can be a potential driver of income inequality because societies in which similar earners intermarry are more unequal than those in which high earners marry low earners (Esping-Andersen 2007;Schwartz 2010;2013). Education is an important factor that affects the social status of individuals and consequently the level of economic inequalities (Sweeney and Cancian 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation